Urolift – minimally invasive surgical BPH management. (4th March 2017) - Pushkaran, Anish; Stainer, Victoria; Muir, Gordon; Shergill, Iqbal S.
ABSTRACT: Introduction : An ideal treatment option for symptomatic Benign Prostatic Hyperplasia (BPH) should relieve lower urinary tract symptoms (LUTS) and restore Quality of Life (QoL). Currently available medical therapies and surgical options for symptomatic BPH have side effects that adversely affects quality of life. Prostatic urethral lift (PUL) is a novel endourology procedure that promises to relieve LUTS without the aforementioned side effects. Areas covered : We diligently reviewed all the published literature on PUL, till July 2016 using standard search criteria. Expert commentary : There is good quality evidence to establish the efficiency of PUL in treating symptomatic BPH without adversely affecting the QoL. Based on the current literature, PUL can be considered as an option for those symptomatic BPH patients with small or medium size prostates (< 80 ml) without median lobe enlargement, who failed on medical therapy or are intolerant to it and wish to preserve their sexual function.